A Rare Cause of Testicular Metastasis: Upper Tract Urothelial Carcinoma. (10th July 2014) - Manav, Alper Nesip; Kazan, Ercan; Ertek, Mehmet Şirin; Amasyalı, Akın Soner; Çulhacı, Nil; Erol, Haluk
Abstract : Metastatic testicular cancers are rare. Primary tumor sources are prostate, lung, and gastrointestinal tract for metastatic testicular cancers. Metastasis of urothelial carcinoma (UC) to the testis is extremely rare. Two-thirds of upper tract urothelial carcinoma (UTUC) is of invasive stage at diagnosis and metastatic sites are the pelvic lymph nodes, liver, lung, and bone. We report a rare case of metastatic UTUC to the testis which has not been reported before, except one case in the literature. Testicular metastasis of UC should be considered in patients with hematuria and testicular swelling.